Omnibus Law Sentiment and its Impact on the Halal Certification Program in Indonesia - Mohamad Nur Efendi; Kusnul Ciptanila Yuni K; Iza Hanifuddin; Arian Agung Prasetiyawan (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
This study aims to determine the sentiments of scholars in Indonesia regarding research and studies that address the topic of Omnibus Law. The data analyzed was in the form of research publications related to the Omnibus Law, with as many as 60 articles spanning 2017 to 2020. Based on the analysis results, the assessment of texts related to Omnibus Law in Indonesia shows a positive sentiment of 40%, a neutral sentiment of 32%, and a negative sentiment of 28%. The optimistic view discusses the importance of the Omnibus Law, which summarizes the bureaucracy and solves the many overlapping regulations. Negative sentiment has given much criticism about the passage of the Omnibus Law, which is inappropriate, not transparent, and controversial, such as the Job Creation Bill. Meanwhile, neutral sentiment is in an intermediary position, namely discussing the positive sides of the Omnibus Law but also criticizing things that are not quite right and providing solutions and suggestions. Intellectual sentiment shows the highest positive and contrasts public sentiment in demonstrations due to disappointment with implementing the Omnibus Law. As an effort to cut bureaucracy, the Omnibus Law also discusses and regulates halal certification. The Omnibus Law's existence has positively influenced accelerating the halal certification process in Indonesia, especially targeting the micro and small business sectors. This aligns with Indonesia's optimistic mission to become the center of the world's halal industry in 2024